Coded excitation using periodic and unipolar M-sequences for photoacoustic imaging and flow measurement - Zhang, Haichong K.; Kondo, Kengo; Yamakawa, Makoto; Shiina, Tsuyoshi (Optics express, 2016)
Photoacoustic imaging is an emerging imaging technology combining optical imaging with ultrasound. Imaging of the optical absorption coefficient and flow measurement provides additional functional information compared to ultrasound. The issue with photoacoustic imaging is its low signal-to-noise ratio (SNR) due to scattering or attenuation; this is especially problematic when high pulse repetition frequency (PRF) lasers are used. In previous research, coded excitation utilizing several pseudorandom sequences has been considered as a solution for the problem. However, previously proposed temporal coding procedures using Golay codes or M-sequences are so complex that it was necessary to send a sequence twice to realize a bipolar sequence. Here, we propose a periodic and unipolar sequence (PUM), which is a periodic sequence derived from an m-sequence. The PUM can enhance signals without causing coding artifacts for single wavelength excitation. In addition, it is possible to increase the temporal resolution since the decoding start point can be set to any code in periodic irradiation, while only the first code of a sequence was available for conventional aperiodic irradiation. The SNR improvement and the increase in temporal resolution were experimentally validated through imaging evaluation and flow measurement.